Karakterisasi, Skrining dan Uji Aktivitas Antibakteri Ekstrak Etanol Bunga Kecombrang (Etlingera elatior (Jack) R.M.Sm) terhadap Staphylococcus aureus - Khairunnisa , Ardina; Yuniarti, Rafita; Dalimunthe, Gabena Indrayani; Rani, Zulmai (Journal of Pharmaceutical and Sciences, 2025)
Background: Torch ginger (Etlingera elatior (Jack) R.M.Sm) is a traditional medicinal plant with potential antibacterial properties due to its secondary metabolites, such as flavonoids, tannins, and terpenoids. Staphylococcus aureus is a pathogenic bacterium causing various infections, and increasing antibiotic resistance necessitates alternative treatments. This study aims to explore the antibacterial potential of torch ginger flower ethanol extract against S. aureus. Objective: This research aimed to characterize the phytochemical content of torch ginger flowers, screen for bioactive compounds, and evaluate their antibacterial activity against S. aureus. Methods: The study employed an experimental design, including phytochemical screening, ethanol extraction (maceration), and antibacterial testing using the disk diffusion method at concentrations of 10%, 30%, 50%, 70%, and 90%. Data were analyzed using one-way ANOVA. Results: Phytochemical screening revealed the presence of alkaloids, flavonoids, tannins, saponins, steroids/triterpenoids, and glycosides. The ethanol extract exhibited antibacterial activity against S. aureus, with inhibition zones of 11.9 mm (weak) at 10%, 16.1 mm (moderate) at 30%, and 21.3–22.5 mm (strong) at 50–90%. Statistical analysis confirmed significant differences (p < 0.05) between concentrations. Conclusion: Ethanol extract of torch ginger flowers demonstrated dose-dependent antibacterial activity against S. aureus, supporting its potential as a natural antibacterial agent.